Triple impact assessments of the 2013 European athletics indoor championship in Gothenburg*. Issue 2 (2nd April 2016) - Andersson, Tommy D.; Armbrecht, John; Lundberg, Erik
ABSTRACT: This study answers the call for holistic assessments of events' sustainability through testing a model for measuring impacts of a sports tourism event from sustainability perspectives and in a common monetary metric. The aim is to achieve commensurability through integration of economic, sociocultural and environmental impacts. Concepts such as use- and non-use value, consumer surplus, direct economic impacts, ecological footprint analysis and shadow cost are applied to fulfil this aim. The model is tested on a three-day long European athletics indoor championship 2013 and the results demonstrate a possibility to produce a sustainability impact analysis in a uniform metric. Measured in monetary terms, sociocultural impacts carry more weight than economic impacts do, whereas environmental impacts have little importance for the total assessment. The assessment of event impacts in one common metric paves the way for destinations to trade-off alternatives and develop clear-cut strategies to increase social, economic and environmental welfare. It is suggested that prices on the market for emission rights severely underestimate environmental costs.